Noc na bagnach Luizjany - Roberts, Nora. (Warszawa : Swiat Ksiazki, 2003)
Polish translation of "Midnight bayou". A romantic suspense novel set in the Bayou country of Louisiana.
Translation of: Midnight Bayou.
Keywords: Home ownership -- Fiction; New Orleans (La.) -- Fiction